2016
DOI: 10.1038/nrn.2015.30
|View full text |Cite
|
Sign up to set email alerts
|

Vicarious trial and error

Abstract: When rats come to a decision point, they sometimes pause and look back and forth as if deliberating over the choice; at other times, they proceed as if they have already made their decision. In the 1930s, this pause-and-look behaviour was termed ‘vicarious trial and error’ (VTE), with the implication that the rat was ‘thinking about the future’. The discovery in 2007 that the firing of hippocampal place cells gives rise to alternating representations of each of the potential path options in a serial manner dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

38
537
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 414 publications
(577 citation statements)
references
References 164 publications
(375 reference statements)
38
537
0
2
Order By: Relevance
“…After the emergence of vision above the water line, the total volume of space monitored by vision in daylight conditions increased 1 million-fold over that of water in full sunlight, enabling (although not necessitating) complex "deliberative mode" strategies (29,53,55) with respect to the most unpredictable features of our environment: other animals. Emergence onto land, with its complex environmental geometry (56) featuring multiple paths toward prey or away from predators, would have furthered the selective benefit of more complex control strategies that take more time to compute than the simplest reactive strategies.…”
Section: Implications Of Long-range Vision For Reactive Neural Circuimentioning
confidence: 99%
See 1 more Smart Citation
“…After the emergence of vision above the water line, the total volume of space monitored by vision in daylight conditions increased 1 million-fold over that of water in full sunlight, enabling (although not necessitating) complex "deliberative mode" strategies (29,53,55) with respect to the most unpredictable features of our environment: other animals. Emergence onto land, with its complex environmental geometry (56) featuring multiple paths toward prey or away from predators, would have furthered the selective benefit of more complex control strategies that take more time to compute than the simplest reactive strategies.…”
Section: Implications Of Long-range Vision For Reactive Neural Circuimentioning
confidence: 99%
“…With the evolution of suitable brain circuitry, certain animals were able to consider multiple options for pursuit or evasion that are likely to enhance fitness, such as by vicarious trial and error behavior in rodents, in which future possibilities are imagined (53,64). Vicarious trial and error, like other forms of prospective cognition or "mental time travel," are dependent on the hippocampus.…”
Section: Implications Of Long-range Vision For Reactive Neural Circuimentioning
confidence: 99%
“…In short, dynamical patterns of neuronal activations that code for behavioural trajectories (i.e., sequence of place cells) are observed in the rodent hippocampus both when animals are actively engaged in overt spatial navigation, and when they are disengaged from the sensorimotor loop, e.g., when they sleep or groom after consuming a food-the latter depending on an internally-generated, spontaneous mode of neuronal processing that generally does not require external sensory inputs. Internally-generated sequences that mimic closely (albeit within different dynamical modes) neuronal activations observed during overt navigation have been proposed to be neuronal instantiations of internal models, which play multiple roles including memory consolidation and planning-thus illustrating a possible way the brain might reuse brain dynamics/internal models in a "dual mode", across overt and covert cognitive processes [132][133][134][135][136][137]. An intriguing neurobiological possibility is that the internal models that produce internally generated sequences are formed by exploiting pre-existing internal neuronal dynamics that are initially "meaningless", but acquire their "meaning" (e.g., code for a specific behavioural trajectory of the animal) through situated interaction, when the internal (spontaneous) and external dynamics become coupled [138].…”
Section: Model-based Approaches To Active Perception and Control: Conmentioning
confidence: 99%
“…As navigational learning increases, attention allocated for sensory precessing decreases and motor-outcome memories play a more prominent role 6,8 . However, the signatures of such learning/relearning and how experience affects them remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…"Response" strategies, on the other hand, rely on the learned sequence of motor-actions to reach a goal-location in a given navigational context. It has been shown that the different stages of spatial learning recruit one or the other strategy, with each using its own distinct, associated neural mechanism (see 6 , for a review on VTE and spatial learning). Specifically, lidocaine inactivation of hippocampal neural populations impaired "place" strategies and striatal caudate nucleus inactivation disrupted "response" navigational strategies 7 .…”
Section: Introductionmentioning
confidence: 99%